Proceedings of 13th International Conference on Pattern Recognition 1996
DOI: 10.1109/icpr.1996.546713
|View full text |Cite
|
Sign up to set email alerts
|

Quoit filter-a new filter based on mathematical morphology to extract the isolated shadow, and its application to automatic detection of lung cancer in X-ray CT

Abstract: We propose a new algorithm named "Qiroit,filter (QPlter~ " to e.vtruct the isolated but low amplitude shudow located in the background which h a y extremely high amplitdeJuctuution. @filter is a kind of mathematical morphology and its formulation is quite simple. This simplicity brings about a unique merit that output from this filter is analytically eqmssivefior the case of analyical input shupes like ball, cone, or rotation of cosine function, which have churucteristics of rotation qwimetry a d monotonic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…From the CT scans, lung regions are extracted by a threshold-based technique [4], and then initial nodule candidates are detected from the lung regions by our methods [8,27,28]. The number of nodule candidates per scan is 93.8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the CT scans, lung regions are extracted by a threshold-based technique [4], and then initial nodule candidates are detected from the lung regions by our methods [8,27,28]. The number of nodule candidates per scan is 93.8.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 illustrates the overview. First, initial nodule candidates are detected from individual slice sections of a thoracic CT scan by our previous detection methods [8,27,28], and then square areas of a certain size are settled on the slice sections so as to comprise the nodule candidates. White squares on a slice section in the leftmost box in the figure show examples of such square areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lead to the requirement of lung nodule detection in chest Computer Tomography (CT) images (Armato et al, 2001) in advance. Thus the Computer Aided Diagnosis (CAD) (Yamamoto et al, 1996;Wiemker et al, 2002) system is very essential for early detection of lung cancer. Early finding of the disease is critical but the truth remains that only 20% of cases are detected in the first phase.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicate that the proposed algorithm detected lung cancer candidates successfully. Yamamoto et al (2000) explained Computer aided diagnosis system with functions to assist comparative reading for lung cancer based on helical CT image. The author have reported that a prototype Computer-Aided Diagnosis (CAD) system (Kanazawa et al, 1998) to automatically detect suspicious regions from chest CT images had been presented and the CT screening system used was a TCT-900 super helix of the Toshiba Corporation.…”
Section: Introductionmentioning
confidence: 99%